2020
DOI: 10.1002/jcp.29883
|View full text |Cite
|
Sign up to set email alerts
|

Pri‐miR‐144 rs9279 is associated with type 2 diabetes and regulation of stress response

Abstract: Single-nucleotide polymorphisms (SNPs) of microRNAs (miRNAs) may alter miRNA expression, binding affinity, and/or messenger RNA expression levels of the target genes, thus leading to disease susceptibility. This study explored the association between SNPs in neuroendocrine stress response-related miRNAs and type 2 diabetes (T2D). In the screening stage, the association between six candidate SNPs of miRNAs and T2D was analyzed in a case-control study including 504 T2D cases and 494 healthy controls. Homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…MirSNP predicts that rs873601-A enhances the binding activity of miR-4715-3p, and rs873601-A decrease the binding activity of miR-4715-3p 29 (Supplementary Figure 3), the polymorphism of target site among in target gene, miRNA or lncRNA could potentially alter stability of binding. 30,31 Together with these, our results confirmed that the rs873601 polymorphism of XPG is associated with susceptibility and biological implications to lung cancer.…”
Section: Discussionsupporting
confidence: 82%
“…MirSNP predicts that rs873601-A enhances the binding activity of miR-4715-3p, and rs873601-A decrease the binding activity of miR-4715-3p 29 (Supplementary Figure 3), the polymorphism of target site among in target gene, miRNA or lncRNA could potentially alter stability of binding. 30,31 Together with these, our results confirmed that the rs873601 polymorphism of XPG is associated with susceptibility and biological implications to lung cancer.…”
Section: Discussionsupporting
confidence: 82%
“…In our previous study, NR3C1 was proved to be a direct target gene of miR-144-3p by luciferase assay ( 24 ). miR-144 has been identified as a stressor-responsive miRNA by several studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, let-7b, miR-142, miR-144, and miR-29a have been identified as neuroendocrine stress response-related biomarkers for T2D and IR ( 23 ). NR3C1 was further identified as a target gene of miR-144 ( 24 ). These evidences suggest that stress-related miRNAs may be potential novel targets for treatment of stress-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…There is now ample evidence in a range of different diseases including pre-eclampsia (Li et al, 2021), type 2 diabetes (Yan et al, 2021), lung fibrosis after lung transplantation (Wang et al, 2020), non-alcoholic fatty liver disease (López-Sánchez et al, 2021), liver cancer (Ghafouri-Fard et al, 2021) and multiple sclerosis (Shareef et al, 2021), that polymorphisms in the relevant miRNA can confer susceptibility and determine the effectiveness of suppression of gene expression. In addition, polymorphisms in the miRNA binding domain of target gene regions play a role in diseases such as colorectal cancer where SNPs in the solute carrier transporter gene predict clinical outcome in colorectal cancer (Bendova et al, 2020) and the KRT81 gene in breast cancer (Sha et al, 2020).…”
Section: Micro-rna Moleculesmentioning
confidence: 99%